Resistance exercise training with protein supplementation improves skeletal muscle strength and improves quality of life in late adolescents and young adults with Barth syndrome: A pilot study. Issue 1 (9th August 2021) - Bohnert, Kathryn L.; Ditzenberger, Grace; Bittel, Adam J.; de las Fuentes, Lisa; Corti, Manuela; Pacak, Christina A.; Taylor, Carolyn; Byrne, Barry J.; Reeds, Dominic N.; Cade, W. Todd
Abstract: Background: Muscle weakness and exercise intolerance contribute to reduced quality of life (QOL) in Barth syndrome (BTHS). Our group previously found that 12 weeks of resistance exercise training (RET) improved muscle strength, however, did not increase muscle (lean) mass or QOL in n = 3 young adults with BTHS. The overall objective of this pilot study was to examine the safety and effectiveness of RET plus daily protein supplementation (RET + protein) on muscle strength, skeletal muscle mass, exercise tolerance, cardiac function, and QOL in late adolescents/young adults with BTHS. Methods: Participants with BTHS (n = 5, age 27 ± 7) performed 12 weeks of supervised RET (60 minutes per session, three sessions/week) and consumed 42 g/day of whey protein. Muscle strength, muscle mass, exercise capacity, cardiac function, and health‐related QOL were assessed pre‐post intervention. Results: RET + protein was safe, increased muscle strength and quality of life, and tended to increase lean mass. Conclusions: RET + protein appears safe, increases muscle strength and quality of life and tends to increase lean mass. Larger studies are needed to confirm these findings and to fully determine the effects of RET + protein in individuals with BTHS.